Preface: Developing an Organization Through Work Life Balance-Driven Leave. Issue 2 (May 2021) - Hammer, Emily
The Problem: Employee leave amidst the Coronavirus pandemic brings about key questions regarding organizational support and development. Current corporate and public policies are written into employee handbooks where they are lauded as supportive economic, social, and sustainable policies for helping people (i.e., workers) achieve humane needs, but are proving to be lacking for truly providing support in the most troubling times. The Solution: The field of Human Resource Management (HRM) and Human Resource Development (HRD) provide unique perspectives on developmental, performance-enhancing, and supportive structures for organizations to thrive. This Issue examines methods for creating truly supportive policies amidst the fallout of the global pandemic not only supports organizational longevity but demonstrates how valued employees truly are within the organization while meeting the labor demands of the market. The Stakeholders: This Special Issue reflects the strong correlation of work-life balance with HRD researchers, administrators and practitioners alike who recognize the value of employee leave and effective policy implementation.